Optical constants and electronic transition in hydrogenated silicon (Si: H) hin films deposited by Layer-by-Layer (LBL) deposition technique - Tong, G.B.; Muhamad, M.R.; Rahman, Saadah Abdul (Penerbit Universiti Kebangsaan Malaysia, 2011)
Optical constants derived from optical transmission (T) and reflectance (R) spectra in the wavelength range of 220 to 2200 nm are presented in this paper for hydrogenated silicon (Si: H) thin films deposited by plasma enhanced chemical vapor deposition (PECVD) using the layer-by-layer (LBL) deposition technique. The films were deposited on quartz substrate by decomposition of SiH4 and H-2 gases at flow-rate of 5 sccm and 20 sccm, respectively. The substrate temperature, deposition pressure and deposition rate are 100 degrees C, 0.8 mbar and 2.8 nm/s, respectively. The as-prepared films were annealed in nitrogen for one hour at annealing temperatures of 400 degrees C, 600 degrees C, 800 degrees C and 1000 degrees C. The as-prepared film thickness of 301 nm decreased to 260 nm when samples were annealed at 1000 degrees C. The refractive indices (similar to 3.0 to 3.4) of annealed films were determined from the interference fringes of transmission spectrum following Manifacier and Davies methods. The electronic transition from valence band to conduction band in these films are characterized from the optical energy gap; E-G (similar to 1.64 to 2.41 eV), the dispersion energy; E-d (similar to 26.4 to 34.0 eV) and the oscillator strength; E-o (similar to 2.8 to 3.2 eV). It is interesting to note that EG is lowest for the films annealed at temperature of 600 degrees C which has the lowest hydrogen content, C-H in the film. Evidence of the presence of nanocrystallites formed in amorphous matrix is also observed for the films annealed at temperatures above 600 degrees C.